PROFIL KADAR MDA PADA TUMOR KULIT MENCIT (Mus musculus) SEBAGAI AKIBAT PEMBERIAN EKSTRAK ETANOL DAUN SIRSAK (Annona muricata L) DAN EKSTRAK METANOL BENALU TEH (Scurulla atropurpurea Bl. Dancer) - Holil, Kholifah (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2013)
Malondialdehyde (MDA) is widely used as an indicator of lipid peroxidation. Increased levels of MDA have been associated with a variety of tumor diseases , one of is a skin tumor. To cope with this disease use several medicinal plants which are leaves of soursop (Annona muricata L) and tea parasite (Scurulla atropurpurea Bl. dancer) . This study aims to determine the profile of MDA in mouse skin tumors as a result of ethanol extract of leaves of soursop and methanol extract of tea parasite. The sample used in this study were mouse skin tumors derived from mice induced by using 7.12 - Dimethilbenz(Î±)Antrasen (DMBA) and ethanol extract of leaves of soursop and methanol extract of tea parasite. While the observation parameters are obtained via MDA spectrophotometer method. The result of this research showed that the levels of MDA in mouse skin tumors induced ethanol extract of leaves of soursop and methanol extract of tea parasite is different. Lowest MDA levels (34.95nmol/g) contained in the DS3 that comes from DMBA-induced mice 25Î¼g/100Î¼l of acetone and ethanol extracts of soursop leaf 60mg/kg